SERTIFIKASI DOSEN DALAM PERSPEKTIF SISTEM PENGUKURAN KINERJA DAN PEMBENTUKAN MENTAL MODEL - Fransiskus Eduardus Daromes; Suwandi Ng . (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
Lecturer certification is a process and forms of recognition of a faculty member associated with qualification, competenceand contribution that deserve to be called a professional lecturer. This study aims to empirically examine the effect ofcertification on faculty members in the perspective of performance measurement systems to psychological empowermentand mental model building and subsequent impact on the performance of the lecturer. The research model was built on thebasis of goal setting theory. We collected data using a mail survey on lecturers who have been certified in the province ofSouth Sulawesi, Indonesia. The selection of respondents was based on the consideration that the respondent hasexperienced the whole certification process and have benefited directly and carry out the legal consequences of thecertification. Data analysis was conducted using structural equation modeling. The results showed that the measurementsystem on lecturers certification have both positive and significant relationship to the dimensions of psychologicalempowerment and the mental models. Further more, mental models have positive and significant influence on theperformance of the lecturer. Similarly, the dimensions of psychological empowerment were positively related to managerialperformance, but only the dimension of meaning tha thave a significant effect. The research findings reveal importance ofbehavioral aspects in deciding lecturer certification systems during the certification process and the implementation.Further more, this paper contributes to the literature on lecturer certification, performance measurement systems, andmental models.Keywords: lecturer certification, performance measurement systems, mental model, and psychological empowerment,lecturers’ performance